2020
DOI: 10.1029/2019tc005974
|View full text |Cite
|
Sign up to set email alerts
|

Oligocene Deformation of the Chuandian Terrane in the SE Margin of the Tibetan Plateau Related to the Extrusion of Indochina

Abstract: Mechanisms driving the tectonic evolution of the southeast (SE) margin of Tibet include the Paleogene extrusion of the coherent Indochina lithospheric block and the continuous deformation caused by lower crustal flow since the middle Miocene. The timing and style of regional deformations are keys to determining the role of each mechanism. Fault‐bounded and fault‐controlled Cenozoic basins within the SE margin of Tibet record regional deformation, surface uplift, and variations in paleoclimate but often are poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 82 publications
(197 reference statements)
1
29
2
1
Order By: Relevance
“…The Hengduan Mountains lie in an area on the south-eastern margin of the modern Tibetan Plateau, accommodating the eastward extrusion of parts of the Qiangtang Terrane and the Indo-China and Chuandian blocks ( Li et al., 2020b , c ; Searle et al., 2011 ; Tapponnier et al., 1982 , 2001 ; Tong et al., 2017 ). This area has experienced strong episodic deformation since the late Cretaceous ( Cao et al., 2019 ; Liu-Zheng et al., 2018 ; Tian et al., 2014 ; Wang et al., 2012 , 2018 ), resulting in several major strike-slips fault systems, tightly folded synclines and anticlines ( YBGMR, 1990 ; Burchfiel and Chen, 2012 ), and a complex of regional high elevation but low-relief relictual landscapes that have become deeply dissected by large rivers draining from the plateau ( Clark et al., 2006 ; Liu-Zheng et al., 2008 ).…”
Section: The Topographic Evolution Of the Tibetan Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Hengduan Mountains lie in an area on the south-eastern margin of the modern Tibetan Plateau, accommodating the eastward extrusion of parts of the Qiangtang Terrane and the Indo-China and Chuandian blocks ( Li et al., 2020b , c ; Searle et al., 2011 ; Tapponnier et al., 1982 , 2001 ; Tong et al., 2017 ). This area has experienced strong episodic deformation since the late Cretaceous ( Cao et al., 2019 ; Liu-Zheng et al., 2018 ; Tian et al., 2014 ; Wang et al., 2012 , 2018 ), resulting in several major strike-slips fault systems, tightly folded synclines and anticlines ( YBGMR, 1990 ; Burchfiel and Chen, 2012 ), and a complex of regional high elevation but low-relief relictual landscapes that have become deeply dissected by large rivers draining from the plateau ( Clark et al., 2006 ; Liu-Zheng et al., 2008 ).…”
Section: The Topographic Evolution Of the Tibetan Regionmentioning
confidence: 99%
“…However, recent radiometric dating of the Jianchuan, Lühe, and Markam basins have shown them all to be late Paleogene and not Neogene ( Gourbet et al., 2017 ; Linnemann et al., 2018 ; Su et al., 2018 ), and not only does this make the fossil floras they host older, but also moves the dates of basin formation back to be coincidental with the onset of movement along major fault systems (e.g. the Ailoshan-Red River) near the end of the Eocene ( Cao et al., 2011 ; Leloup et al., 1995 ; Tapponnier et al., 1990 ; Li et al., 2020b ). The synchronicity of basin formation and initiation of fault movement in the late Eocene/early Oligocene (~35 Ma) points to a common tectonic mechanism, which appears to have involved semi-rigid re-organisation of eastern Tibet, clockwise rotation of the Indo China Block, and inevitably must have involved significant topographic development ( Li et al., 2020b , c ).…”
Section: The Topographic Evolution Of the Tibetan Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dates showed beyond doubt that the associated 'Miocene' flora was some 20 million years older than previously thought based on the modern aspect of the component leaves, seeds and pollen (Zhang et al 2007;Xu et al 2008;Huang et al 2016;Tang et al 2020). Further finds of ashes near the base of the nearby Luhe coal mine have yielded 40 Ar/ 39 Ar ages for biotites and feldspars of~33 Ma (Li et al 2020), and thus match the U-Pb dates obtained by Linnemann et al (2018) and those of detrital zircons found in fluvial sands higher within the mine section (Wissink et al 2016). Coupled with palaeomagnetostratigraphy, these ages suggest the Lühe Basin evolved between~35 and 26.5 Ma, and constrain the onset of movement of the basin-bounding Chuxiong fault to 35 Ma (Li et al 2020).…”
Section: Dating Is Everythingmentioning
confidence: 80%
“…Further finds of ashes near the base of the nearby Luhe coal mine have yielded 40 Ar/ 39 Ar ages for biotites and feldspars of~33 Ma (Li et al 2020), and thus match the U-Pb dates obtained by Linnemann et al (2018) and those of detrital zircons found in fluvial sands higher within the mine section (Wissink et al 2016). Coupled with palaeomagnetostratigraphy, these ages suggest the Lühe Basin evolved between~35 and 26.5 Ma, and constrain the onset of movement of the basin-bounding Chuxiong fault to 35 Ma (Li et al 2020). This demonstrates that the onset of fault movement was contemporaneous with initiation of the Ailaoshan-Red River fault system (Tapponnier et al 1990;Leloup et al 1995;Cao et al 2011) and suggests a common, region-wide, cause.…”
Section: Dating Is Everythingmentioning
confidence: 99%